1995
DOI: 10.1002/hep.1840220104
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the surgical results in patients with hepatitis B versus hepatitis C-related hepatocellular carcinoma

Abstract: To assess the differences in the surgical results between patients with hepatitis B- and hepatitis C-related hepatocellular carcinoma (HCC), the operative outcomes of 30 patients with hepatitis B surface antigen (HBsAg)-positive (the B-HCC group) and 96 patients with hepatitis C antibody (HCVAb)-positive (the C-HCC group), who had undergone hepatic resection from 1989 to 1993, were compared. The mean age of the patients in the C-HCC group was higher than that in the B-HCC group (61.7 years vs. 57.0 years, P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
47
2
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 26 publications
9
47
2
1
Order By: Relevance
“…However it has been widely evaluated and showed low prognostic significance regarding HCC recurrence after hepatic resection for both HCV and HBV related HCCs [10,13,16,30]. Few studies had shown that pTNM staging provides a significant predictor for recurrence in HCV related HCCs [3] and HBV related HCCs [9,11,31]. This significant correlation was similar to the findings in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However it has been widely evaluated and showed low prognostic significance regarding HCC recurrence after hepatic resection for both HCV and HBV related HCCs [10,13,16,30]. Few studies had shown that pTNM staging provides a significant predictor for recurrence in HCV related HCCs [3] and HBV related HCCs [9,11,31]. This significant correlation was similar to the findings in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In our study tumour recurrence occurred in 88 patients (42.3%) and most recurrences occurred in the liver (77.3%). The cumulative recurrence rates of HCV related HCCs are higher than HBV related HCCs [9][10][11]. This could be explained by the high viral replication and hepatic inflammation in HCV related HCCs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mean age at detection of HCC is lower for patients with HBsAg alone than for patients with HCV infection. 7,14,15,49) The likelihood of multicentric carcinogenesis is low in patients with HBsAg, because the HCC often develops before cirrhosis. 11,49) The results in this study indicate that the clinicopathological criteria for multicentric HCC are of practical value and that HCV infection and a combination of current HCV infection and prior infection of HBV (perhaps with an integrated HBV gene or genes) are strong risk factors for multicentric HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the incidence of HCC in patients with HCV or HBV affects decisions about treatment, because these viruses are factors in the outcome after surgery. 14,15) HCV-related HCCs tend to be multifocal, 7,9) but no large-scale studies on the incidence of and risk factors for multicentric occurrence of HCC have been reported. We retrospectively evaluated criteria for identification of multicentric HCCs from clinicopathological findings, examined the clinical differences among patients with single HCC, multicentric HCCs, and HCCs with intrahepatic metastasis, and investigated risk factors in multicentric carcinogenesis, especially the roles of HCV and HBV.…”
mentioning
confidence: 99%